2001
DOI: 10.1191/026921501676849095
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of quadriceps training after proximal femoral fracture

Abstract: Progressive high-intensity quadriceps training in elderly proximal femoral fracture patients increased leg extensor power and reduced disability. This was accompanied by an increase in energy as measured by the Nottingham Health Profile. This intervention may provide a simple practical way of improving outcome in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
108
3
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 18 publications
3
108
3
2
Order By: Relevance
“…Hip fractures are associated with poorer survival [1] , a greater than 50% loss of fractured lower limb strength within a few week after surgery [2][3][4] and the return of only poor functional mobility within 4 mo [5] . Knee extensor muscle strength is an independent predictor of falls within 6 mo of hip fracture [6] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hip fractures are associated with poorer survival [1] , a greater than 50% loss of fractured lower limb strength within a few week after surgery [2][3][4] and the return of only poor functional mobility within 4 mo [5] . Knee extensor muscle strength is an independent predictor of falls within 6 mo of hip fracture [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Some trials have suggested the benefits of exercise after hip fracture [8] , but studies have most often commenced as extended programmes after standard physical therapy has ceased, 6 to 8 wk after fracture at the earliest [9][10][11][12][13][14][15][16] . To our knowledge, only one study has evaluated the effects of early 6-wk (median of 15 d postsurgery) strength training after hip fracture as an inpatient rehabilitation programme [3] . However, no similar studies have been conducted in community-dwelling geriatric patients with hip fractures or have succeeded in promoting the regaining of symmetrical lower limb muscle strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decades, resistance training has emerged as an effective method to induce muscle hypertrophy and increase muscle strength and functional performance in frail elderly (12,21) and in patients with chronic diseases (10,23,26). Furthermore there is increasing evidence that resistance training used in the late postoperative phase is an effective method to restore muscle function in elderly patients (22,34,42). Despite this, resistance training is still rarely used in the rehabilitation of elderly patients and especially in the elderly who have been hospitalized.…”
mentioning
confidence: 99%
“…Interestingly, it has been suggested that increasing muscle strength and power by resistance training may also reduce pain in osteoarthritis 35 . Supervised progressive resistance training is feasible and effective within a few months in healthy older women 28 , in frail older people 36 , and in clinical populations 35 , even shortly after surgery 37 or hip fracture 38 . In addition, it may be beneficial for mobility in people with mobility limitation [35][36][37][38][39] and may therefore be a potentially effective intervention when included in the rehabilitation protocol.…”
Section: Discussionmentioning
confidence: 99%